Types of individual religiosity: theoretical and empirical study of dispositional and operational characteristics - Yaroschuk, Marianna (Psychological Prospects Journal, 2017)
The primary problems of empirical study of individual religiosity are highlighted in the article. They are represented by psychometric validity of methods, representative content of the samples, cross-cultural opportunities of the research. The religiosity is treated as fulfillment of religious believes and practices in the certain religious institutions and spirituality is treated as a phenomenon with personal and experiential connotations. The spirituality without religiosity is analyzed. Two levels of religiosity are defined. Among them there is dispositional level represented by the personality traits, types of intuitions (inferential, affective and holistic) and operational level represented by self-regulation of emotions while interpersonal interaction. The results of the factor analysis allow revealing seven types of individual religiosity: religious-moral, religious-anxious, religious-formal, religious-intuitive, religious-normative, religious-conservative types. The types of individual religiosity have different dispositional characteristics: sensitiveness, conservativeness, empathy, anxiety, inferential, affective and holistic types of intuition, and various interactional characteristics based on emotional self-regulation: predominance of positive/negative emotions, self-regulation of emotion, degree of emotions brightness, emotional distance. The primary prospects of the further research are studies of individual religiosity as a personality trait of emotional and intuitive sphere.
Keywords: religiosity of personality, dispositional level, operational level, interpersonal interaction, personality traits.